The Ecology of Language in Multilingual India Voices of Women and Educators in the Himalayan Foothills - Groff, Cynthia (Palgrave Studies in Minority Languages and Communities, 2018)
This book explores the linguistic ecology of the Kumaun region of Uttarakhand, India through the experiences and discourses of minority youth and their educators. Providing in-depth examples of Indian multilingualism, theis volume analyses how each language is valued in its own context; how national-level policies are appropriated and contested in local discourses; and how language and culture influence educational opportunities and identity negotiation for Kumauni young women. In doing so, the author examines how students and educators navigate a multilingual society with similarly diverse classroom practices. She simultaneously critiques the language and education system in modern India and highlights alternative perspectives on empowerment through the lens of a unique Gandhian educational context. This volume allows Kumauni women and their educators to take centre stage, and provides a thoughtful and nuanced insight into their minority language environment. This unique book is sure to appeal to students and scholars of multilingualism, sociolinguistics, language policy and minority languages. Cynthia Groff is Guest Researcher at Leiden University, Netherlands. A graduate of the University of Pennsylvania's Graduate School of Education, she has conducted post-doctoral research through Université Laval, Québec, Canada, and the Universidad Autónoma Metropolitana-Iztapalapa, Mexico.